The Banach contraction principle: generalizations, extensions and its inverse (Letters in Nonlinear Analysis and its Applications, 2024)
In this work, we give several generalizations and extensions of the Banach contraction principle. Its inverse is also studied. The extension is based on weaker topologies. Particularly, we focus on partial metric spaces and b-metric spaces.
Keywords: Fixed point technique; contraction; (generalized) metric space; general topology